2002
DOI: 10.1186/1471-2156-3-19
|View full text |Cite
|
Sign up to set email alerts
|

SNP frequency, haplotype structure and linkage disequilibrium in elite maize inbred lines

Abstract: Background: Recent studies of ancestral maize populations indicate that linkage disequilibrium tends to dissipate rapidly, sometimes within 100 bp. We set out to examine the linkage disequilibrium and diversity in maize elite inbred lines, which have been subject to population bottlenecks and intense selection by breeders. Such population events are expected to increase the amount of linkage disequilibrium, but reduce diversity. The results of this study will inform the design of genetic association studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
3
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(116 citation statements)
references
References 44 publications
(53 reference statements)
10
97
3
2
Order By: Relevance
“…It was shown that allelic variants at this locus consisted of haplotypes rather than single base replacements. Similar studies on haplotyping were conducted earlier in bread wheat (Caldwell et al 2004;Beales et al 2005), barley (Bundock & Henry 2004;Russell et al 2004) and maize (Ching et al 2002;Palaisa et al 2003). Taken together, these studies suggest that on average there are fewer SNPs/haplotype in inbreeders like wheat and barley than in outbreeders like maize (Clark et al 2004;Jung et al 2004;Palaisa et al 2004;Buntjer et al 2005).…”
Section: Haplotype Structuresupporting
confidence: 75%
“…It was shown that allelic variants at this locus consisted of haplotypes rather than single base replacements. Similar studies on haplotyping were conducted earlier in bread wheat (Caldwell et al 2004;Beales et al 2005), barley (Bundock & Henry 2004;Russell et al 2004) and maize (Ching et al 2002;Palaisa et al 2003). Taken together, these studies suggest that on average there are fewer SNPs/haplotype in inbreeders like wheat and barley than in outbreeders like maize (Clark et al 2004;Jung et al 2004;Palaisa et al 2004;Buntjer et al 2005).…”
Section: Haplotype Structuresupporting
confidence: 75%
“…The selective sweep covering Ͼ0.5 Mb is much broader than the domestication-related selective sweep observed at tb1 (7). The extent of LD in the region may be the largest reported to date in maize (27)(28)(29)(30). This is presumably the result of the qualitative nature of the trait, the short time since the selection was imposed, and partial genetic isolation of the yellow germplasm after selection (8).…”
Section: Discussionmentioning
confidence: 94%
“…If the causative mutation is not genotyped, it is still possible to identify association via markers that are in LD with the causative mutation. However, the extent of LD can vary dramatically among plant species (53,54), among genomic regions within plants (55), and among population samples (56)(57)(58). The distribution of LD is also affected by homologous gene conversion, which predominantly disrupts short-range LD patterns (43,59,60).…”
Section: From the Top Down: Qtl And Ld Mappingmentioning
confidence: 99%